Contribution of Self-Concept and Social Skills Toward Students' Social Relationships - Batubara, Juliana; Daharnis, Daharnis; Susanto, Eko (Kuras Institute, 2025)
Social relationships result from interactions between individuals influenced by various factors, including self-concept, social skills, parenting patterns, culture, and communication. This study aims to analyze (1) the contribution of self-concept to students' social relationships, (2) the contribution of social skills to students' social relationships, and (3) the simultaneous contribution of self-concept and social skills to students' social relationships at Islamic High School of Insan Cendekia Padang Pariaman, Indonesia. This research method is ex post facto using a questionnaire that has been tested for validity and reliability as a data collection instrument. The research sample consisted of 96 students who were selected randomly. Data analysis shows that both partially and simultaneously, self-concept and social skills significantly contribute to students' social relationships. This finding emphasizes the importance of strengthening self-concept and social skills to build harmonious social relationships among students.